Film production theory - Geuens, Jean Pierre (SUNY series, cultural studies in cinema/video., 2000)
"Most serious film books during the last twenty years have focused on theoretical issues, film history, or film analyses, leaving production to the side. This text, however, appropriate for film production courses, fills that void, opening the production process to pertinent, argumentative notions and incorporating material from Heidegger, Merleau-Ponty, and Derrida, among others. Although Geuens covers screenwriting, lighting, staging, and framing, among other production issues, he avoids the strictly vocational or "professional" approach to film teaching currently applied to most production courses."--Print version book jacket